2008
DOI: 10.2337/dc08-1038
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Correlates of the Increasing Trend in Prevalence of Gestational Diabetes Mellitus in a Large Population of Women Between 1995 and 2005

Abstract: OBJECTIVE -Gestational diabetes mellitus (GDM) is an increasingly prevalent risk factor for the development of type 2 diabetes in the mother and is responsible for morbidity in the child. To better identify women at risk of developing GDM we examined sociodemographic correlates and changes in the prevalence of GDM among all births between 1995 and 2005 in Australia's largest state. ] for decreasing socioeconomic status quartiles). Increasing age was strongly associated with GDM, with women aged Ͼ40 years havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
226
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(249 citation statements)
references
References 17 publications
22
226
0
1
Order By: Relevance
“…Other recent studies have reported a weak impact of BMI on risk of T2D in a low income country (21). Increasing age is major risk factor for T2D (22,23). Increasing age was independently associated with increasing FPG but not significantly with increased 2-h PG levels in the linear regression analysis including all 5100 pregnant North Indian women.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Other recent studies have reported a weak impact of BMI on risk of T2D in a low income country (21). Increasing age is major risk factor for T2D (22,23). Increasing age was independently associated with increasing FPG but not significantly with increased 2-h PG levels in the linear regression analysis including all 5100 pregnant North Indian women.…”
Section: Discussionmentioning
confidence: 80%
“…While follow-up studies of mothers and offspring are planned for the future, it needs to be emphasized that such studies will not answer the most crucial questions of the causality of adverse outcomes associated with GDM. A meta-analysis from 2008 concluded that there is insufficient evidence to show beneficial effects of intensive glucose-lowering treatment for long-term adverse GDM complications, including risk of dysmetabolic traits in the offspring (23). Importantly, it was mentioned that potential residual confounding risk factors such as educational status, body fat content and distribution, urbanisation, etc., and not necessarily elevated plasma glucose level per se, might be responsible for some adverse pregnancy outcomes associated with GDM.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…A large Australian study demonstrated that women born in East or South Asia had an increased risk of developing GDM relative to women born in Australia (ORs 3.2 and 4.2, Results are presented as %, unless stated otherwise respectively) [27]. Similarly, a smaller study in New York City demonstrated an increased risk of GDM among virtually all minority populations compared with whites, including an adjusted relative risk of 2.3 for Chinese women and 4.7 for South Asian women [28].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of gestational diabetes mellitus is not well-understood. The pathogenesis of gestational diabetes mellitus involves many complex environmental and lifestyle factors, such as pregnancies at an older age, high pre-pregnancy weight and BMI, hydramnios, a history of gestational diabetes mellitus, a history of type 2 diabetes, vaginal candida infection, and a history of gestational diabetes (Kühl, 1991;Damm, 1998;Kopp, 2005;Anna et al, 2008;Savitz et al, 2008;Sella et al, 2013;Moon et al, 2015). However, not all pregnant women exposed to certain risk factors go on to develop gestational diabetes mellitus, suggesting that hereditary factors may contribute to the occurrence of this disease.…”
Section: Introductionmentioning
confidence: 99%